2011
DOI: 10.1097/fpc.0b013e3283498ecf
|View full text |Cite
|
Sign up to set email alerts
|

Genetic epidemiology of induced CYP3A4 activity

Abstract: To our knowledge, this is the first genetic epidemiological study of induced CYP3A4 activity. Our results motivate further research to identify common and rarer genetic variants that underpin the heritable component of variation in induced CYP3A4 activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 28 publications
1
39
0
3
Order By: Relevance
“…Notwithstanding the counteracting immunosuppressive effect of HIV/smoking on the efficacy of therapy, other possible causes of smoking-related interference with HAART include 1) smoking is a surrogate marker of a noncompliant disposition [81,82]; 2) higher frequencies of side-effects in smokers, including neuropsychiatric symptoms associated with efavirenz-based HAART regimens [83]; 3) negative effects of smoking-related activation of cytochrome P450 enzymes, such as the CPY1A1-m1 variant, which promote oxidative conversion of smoke-derived toxicants to DNA adducts, causing activation of genes that support HIV replication [70,84]; 4) altered pharmacokinetics of antiretroviral agents, possibly related to smoking-mediated induction of CYP3A4 and aryl-hydrocarbon-hydroxylases [85,86], which metabolise many protease and non-nucleoside reverse transcriptase inhibitors [87,88]; and 5) smoking-induced mitochondrial oxidative stress [89], which may exacerbate the adverse effects of antiretroviral drugs that induce mitochondrial toxicity, such as drugs from the nucleoside reverse transcriptase inhibitor class [90].…”
Section: Effects Of Smoking On Hiv Disease Progression and Treatmentmentioning
confidence: 99%
“…Notwithstanding the counteracting immunosuppressive effect of HIV/smoking on the efficacy of therapy, other possible causes of smoking-related interference with HAART include 1) smoking is a surrogate marker of a noncompliant disposition [81,82]; 2) higher frequencies of side-effects in smokers, including neuropsychiatric symptoms associated with efavirenz-based HAART regimens [83]; 3) negative effects of smoking-related activation of cytochrome P450 enzymes, such as the CPY1A1-m1 variant, which promote oxidative conversion of smoke-derived toxicants to DNA adducts, causing activation of genes that support HIV replication [70,84]; 4) altered pharmacokinetics of antiretroviral agents, possibly related to smoking-mediated induction of CYP3A4 and aryl-hydrocarbon-hydroxylases [85,86], which metabolise many protease and non-nucleoside reverse transcriptase inhibitors [87,88]; and 5) smoking-induced mitochondrial oxidative stress [89], which may exacerbate the adverse effects of antiretroviral drugs that induce mitochondrial toxicity, such as drugs from the nucleoside reverse transcriptase inhibitor class [90].…”
Section: Effects Of Smoking On Hiv Disease Progression and Treatmentmentioning
confidence: 99%
“…A recent genetic epidemiology study estimated the heritability of induced CYP3A4 activity at 66%, implying that genetic factors do play a large role, but environmental factors such as smoking and BMI may also significantly influence enzymatic activity [203]. Indeed, a different study found that patient weight explained 35% of the variability in cyclosporine oral clearance, and concomitant use of prednisolone at doses 20 mg/day or higher was also associated with higher clearance of the drug.…”
Section: Influence On Cyclosporine Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 99%
“…4,5 With respect to genetic factors, twin studies and repeated drug administration approaches have estimated a high degree of heritability in the CYP3A4 interindividual variation. [6][7][8] In this regard, the Human CYP Allele Nomenclature Database includes 26 different CYP3A4 variant proteins. Three are truncated proteins resulting from rare premature stop codons (CYP3A4*6, CYP3A4*20 and CYP3A4*26 alleles), 9,10,11 whereas the rest are low-frequency/rare missense variants, some with reduced enzymatic activity (e.g.…”
Section: Introductionmentioning
confidence: 99%